Turkey´s Pioneering Psychoanalyst: Izeddin Sadan´s Disquisition on (Homosexual) Love as Sickness - Kilic, Gözde; Justus Liebig University Giessen (My University, 2020)
Izeddin Sadan, considered to be among the pioneers of psychoanalysis in Turkey, published a series of essays in 1936 titled Eros (Ask) Ile Mücadele [ Strife with Eros (Love) ] in the popular magazine Yeni Adam. He hailed these essays as a landmark in the scientific endeavor to objectively lay out the true nature of love. In them, he described love as a volatile microbe constituting sickness with its origins in Christianity; however, by inverted logic, he projected the same sickness onto Islam, in particular Sufism, which he disparaged as homosexual debauchery. This article looks at how Sadan´s pathologizing of Sufi love of beardless boys as sexual perversion is itself a symptom of pathology, pointing towards a fundamental change in the gen-dered/modernized/Orientalized subject´s relationship with the other and itself.
Keywords: Izeddin Sadan; Turkey; psychoanalysis; love; sickness; Sufism; homosexuality; nationalism; ddc:300